Research Mapping of Sharia Banking During the Covid-19 Pandemic: Vosviewer Bibliometric and Literature Review - Muhammad Kharis Tambusa; Trimulato Trimulato (Universitas Darussalam Gontor, 2023)
This study’s purpose is to describe the development of research related to Islamic banks during the Covid-19 pandemic. Various published national standard studies on the theme of sharia banking during the Covid-19 pandemic. This research uses the Publish or Perish (POP) application to explore various related studies sourced from Google Scholar. The data used is for 3 years, namely the period from 2020 to 2022. The keywords used in the article search are sharia banking during the Covid-19 pandemic. From the search results, the articles obtained will be inputted into the Vosviewer application, for descriptive analysis, an analysis of the results obtained after being shown by the application is carried out. Then input was carried out in the VOSviewer application, then the results were found from research for three years with the theme of sharia banking during the Covid-19 pandemic. The results showed that from the Vosviwer application, there were 38 articles obtained from the publish or perish (PoP) application, the results of Network Visualization, Overlay Visualization, and Density Visualization. There are 8 clusters, with various items from each cluster. For the literature review, 7 research themes related to sharia Banking during the Covid-19 Pandemic were found.